2018
DOI: 10.5194/os-14-1483-2018
|View full text |Cite
|
Sign up to set email alerts
|

What can seabirds tell us about the tide?

Abstract: Abstract. Small global positioning system (GPS) trackers are now routinely used to study the movement and behaviour of birds at sea. If the birds rest on the water they become “drifters of opportunity” and can be used to give information about surface currents. In this paper, we use a small data set from satellite-tracked razorbills (Alca torda) in the Irish Sea to test the potential of this idea for measuring tidal currents. Razorbills regularly rest on the sea overnight and their tracks at this time are cons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…We first explored whether the presence of LEBs can account for any variation in the counts of seabirds, and then tested specifically for an effect of LEB deployment in a before-after-control-impact (BACI) design analysis-a similar approach was adopted by Jiménez et al [42] in their study assessing seabird bycatch reduction in pelagic longline fleets. Counts of seabirds in a small area are subject to large temporal variation due to diurnal and seasonal movements, temporal disturbances, the influence of tidal currents, wind/weather factors, and other aspects that are difficult to measure [43][44][45]. Due to the large number of potential environmental factors that may affect seabird abundance and the fact that some of these variables may be correlated, we first conducted an exploratory analysis using an analytical approach that can accurately identify the relative importance of variables under these conditions [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…We first explored whether the presence of LEBs can account for any variation in the counts of seabirds, and then tested specifically for an effect of LEB deployment in a before-after-control-impact (BACI) design analysis-a similar approach was adopted by Jiménez et al [42] in their study assessing seabird bycatch reduction in pelagic longline fleets. Counts of seabirds in a small area are subject to large temporal variation due to diurnal and seasonal movements, temporal disturbances, the influence of tidal currents, wind/weather factors, and other aspects that are difficult to measure [43][44][45]. Due to the large number of potential environmental factors that may affect seabird abundance and the fact that some of these variables may be correlated, we first conducted an exploratory analysis using an analytical approach that can accurately identify the relative importance of variables under these conditions [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that further studies combining diving behaviour and movement patterns are likely to confirm that non-ARS foraging is more widespread, particularly in areas of high tidal activity. Interestingly, a study on razorbills in Wales, UK, showed extensive periods of drift and little evidence of ARS, and while foraging behaviour was not the focus of that study [48], birds were diving during these trips (E. Owen 2019, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…The speed threshold was chosen to account for the exceptional current speeds in the channel, regularly exceeding 3.5 m s −1 [45,57,58]. This means that birds drifting passively with the current, a behavior known as tidal drift, could realistically reach groundspeeds normally associated with flight [59][60][61]. An example R script for preparation, processing and analysis (steps 2-4 Figure 2) along with a dataset for one individual are provided in Appendix A and Supplementary Materials.…”
Section: Preparation and Processingmentioning
confidence: 99%
“…The blue shaded area (3.5-5 m/s) is the range of peak current speeds in the Pentland Firth [45,57,58]. Between 1 and 5 m/s, there is therefore a range of speeds that normally could be classified as flight but in this case could be tidal drift (bird sitting on the sea surface and drifting with the tide, [59][60][61]). The cautious approach would therefore be to set a speed threshold of >5 m/s.…”
Section: Appendix A3 Speedmentioning
confidence: 99%